Effect of Different grades of River sand Cement and Copper Slag Cement Matrices on Flexural Behaviourof Ferrocement Slabs (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Ferrocement is a versatile construction material having light weight, closely spaced small diameter reinforcement covered with cement mortar. Lot of works have been carried out onferrocement by using Â river sand as fine aggregate in India and other countries. Research also has been carried out on ferrocement with other than cement mortar. Matrices like polymer impregnated cement mortar, resin mortar, latex modified cement mortar and fibre reinforced mortar matrix and studied their structural responses at CSIR-Structural Engineering Research Centre, Chennai and Nihon University, Japan. Research works on ferrocement is under progress by using copper slag as fine aggregate in cement mortar at Easwari Engineering College, Ramapuram, Chennai. Totally six mortar mixtures, three with river sand and three with copper slag as fine aggregate and three different strength in each were used as matrix in preparation of ferrocement slabs. Reinforcement content was same in all specimens. Mechanical properties, Viz., compressive strength, split tensile strength and flexural strength were evaluated for all the mixtures.To evaluate the effect of different mortar proportions and different types of fine aggregates on flexural behaviour of ferrocement slabs having same size and reinforcement content. The types of fine aggregate used are normal river sand and the same gradation of copper slag. Different mortar mixtures used are 1:1, 1:2 and 1:3 (Cement: Fine Aggregate) and equal volume to river sand of copper slag was used in another three mixtures. Totally 6 mortar mixtures were used and studied their mechanical properties, viz., compressive strength, split tensile strength and flexural strength.